2018
DOI: 10.1016/j.resuscitation.2018.06.028
|View full text |Cite|
|
Sign up to set email alerts
|

Outcomes and healthcare-associated costs one year after intensive care-treated cardiac arrest

Abstract: In-ICU CA patients had the lowest one-year survival with the effective cost per survivor three times higher than for OHCAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…One previous study reported OHCA survivors to have combined pre-, in- and post-hospital healthcare-associated costs of €37,000 in 2013 euros in a 6-month follow-up [31]. In a recent study of single-centre data published by our group, combined in- and post-hospital healthcare costs in 1-year follow-up were €59,000 for OHCA and €84,000 for IHCA hospital survivors in 2013 euros [18].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…One previous study reported OHCA survivors to have combined pre-, in- and post-hospital healthcare-associated costs of €37,000 in 2013 euros in a 6-month follow-up [31]. In a recent study of single-centre data published by our group, combined in- and post-hospital healthcare costs in 1-year follow-up were €59,000 for OHCA and €84,000 for IHCA hospital survivors in 2013 euros [18].…”
Section: Discussionmentioning
confidence: 98%
“…All social insurance reimbursements during the year following hospital admission were included. Effective cost per survivor (ECPS) was calculated by dividing the sum of total costs for all patients with the number of survivors [18]. We adjusted all costs to the value of euro in the year 2013 according to the consumer price index (CPI) in Finland.…”
Section: Methodsmentioning
confidence: 99%
“…The total healthcare cost variable included the index university hospital treatment costs, rehabilitation hospital costs, and social security costs up to 1 year after admission. The cost variables have previously been described in detail [2,16,17]. We adjusted all costs according to the average annual Consumer Price Index in Finland into euros, based on the exchange rate in 2019 (data from Statistics Finland):…”
Section: Outcome and Cost Variablesmentioning
confidence: 99%
“…There are no limits to or recommendations for cost-effective treatments in terms of ECPS or ECPIS, and these measures cannot be directly compared to QALY. Still, compared to severe TBI (with an ECPS of approximately €80,000 and an ECPIS of approximately €145,000 [16,17]), SAH (an ECPS of approximately €70,000, an ECPIS of approximately €95,000 [17]), acute ischemic stroke (an ECPS of approximately €55,000, an ECPIS of approximately €105,000 [17]), and cardiac arrest (an ECPS of approximately €95,000, an ECPIS of approximately €100,000 [2]), ICH surgery seems to be cost-effective in terms of survival, with an ECPS of approximately €110,000, though not in terms of independent living (with an ECPIS of approximately €335,000).…”
Section: Comparison With Previous Studiesmentioning
confidence: 99%
“…Many patients resuscitated from out-of-hospital cardiac arrest (OHCA) suffer from hypoxic-ischaemic brain injury (HIBI) and die in the intensive care unit (ICU) without regaining consciousness [1,2]. Accurate prognostication is of paramount importance to prevent prolonged futile intensive care and, on the other hand, to avoid withdrawal of care in those who have a chance to recover [3,4]. Current guidelines recommend a multimodal approach in the prognostication of cardiac arrest (CA) patients including clinical examination, radiological imaging, neurophysiological assessment, and biomarkers [5].…”
Section: Introductionmentioning
confidence: 99%